2008
DOI: 10.1016/j.cub.2008.07.094
|View full text |Cite
|
Sign up to set email alerts
|

Visually Mediated Motor Planning in the Escape Response of Drosophila

Abstract: A key feature of reactive behaviors is the ability to spatially localize a salient stimulus and act accordingly. Such sensory-motor transformations must be particularly fast and well tuned in escape behaviors, in which both the speed and accuracy of the evasive response determine whether an animal successfully avoids predation [1]. We studied the escape behavior of the fruit fly, Drosophila, and found that flies can use visual information to plan a jump directly away from a looming threat. This is surprising, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
246
4
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(264 citation statements)
references
References 24 publications
11
246
4
3
Order By: Relevance
“…Hindlegs are flexed into a 'cocked' position, which may or may not be followed by an escape jump (Bennet-Clark, 1975;Heitler and Burrows, 1977;Santer et al, 2005). Escape 'preparation' has also been observed in Drosophila flies which, when stimulated, execute postural adjustments so that leg extension will push them away from the stimulus, whether escape will eventually be performed or not (Card and Dickinson, 2008). In these cases, escape preparation is, however, related to either mechanical constraints (locust) or directional advantage (Drosophila), rather than to enhancing locomotor performance as observed here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hindlegs are flexed into a 'cocked' position, which may or may not be followed by an escape jump (Bennet-Clark, 1975;Heitler and Burrows, 1977;Santer et al, 2005). Escape 'preparation' has also been observed in Drosophila flies which, when stimulated, execute postural adjustments so that leg extension will push them away from the stimulus, whether escape will eventually be performed or not (Card and Dickinson, 2008). In these cases, escape preparation is, however, related to either mechanical constraints (locust) or directional advantage (Drosophila), rather than to enhancing locomotor performance as observed here.…”
Section: Discussionmentioning
confidence: 99%
“…The bending response consists of a slow and subtle movement of the tail and usually occurs within seconds of stimulation. It is therefore hypothesised that this bending response may represent an escape 'preparation' as observed in other animals, although based on very different mechanisms (Bennet-Clark, 1975;Card and Dickinson, 2008). Specifically, here we tested the following main hypotheses: (1) whether escape direction and performance in fish startled using lateral mechanical stimuli were affected by the alerting weak stimulation and the resulting changes in postural curvature, (2) whether escape performance in fish startled using a stimulus from above was affected by the alerting weak stimulation and (3) whether fish observed in the field showed any preference in the direction of escape relative to the postural C-bend.…”
Section: Introductionmentioning
confidence: 99%
“…Two types of flight initiation are distinguished in the fruit fly, Drosophila melanogaster Meigen (Diptera: Drosophilidae) -a fast escape in response to threatening visual stimuli and a slow voluntary take-off based on the assessment of a stimulus, in reflection of the internal physiological state of the animal (Trimarchi and Schneiderman 1995;Allen et al 2006;Card and Dickinson 2008). Olfactory cues elicit premeditated flights.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative analysis of escape behaviors (SI Appendix, Fig. S9A) (31) indicated that these escape behaviors were observed frequently in trained males but rarely in naïve males or control males subjected to either pseudorandom laser irradiation or pseudorandom punishment (Fig. 4A).…”
Section: Significancementioning
confidence: 99%